Colchicine protects against cartilage degeneration by inhibiting MMP13 expression via PLC-γ1 phosphorylation. Issue 11 (November 2021) - Takeuchi, K.; Ogawa, H.; Kuramitsu, N.; Akaike, K.; Goto, A.; Aoki, H.; Lassar, A.; Suehara, Y.; Hara, A.; Matsumoto, K.; Akiyama, H.
Summary: Objective: Low molecular weight compounds that reduce the expression of MMP13 at the mRNA level might serve as disease-modifying osteoarthritis (OA) drugs (DMOADs). The objective of this study was to identify a candidate DMOAD that targets MMP13 expression. Design: High-throughput screening was performed to identify compounds that suppress inflammatory cytokine-induced MMP13 expression. Ingenuity pathway analysis (IPA) using isobaric tags for relative and absolute quantification (iTRAQ)-based proteomic analysis was conducted to identify signaling pathways related to cytokines. MMP13 expression in chondrocytes was evaluated through RT-qPCR and western blotting analyses. Additionally, 10-week-old mice were subjected to destabilization of the medial meniscus (DMM) surgery to induce OA and were sacrificed 12 weeks post-surgery for pathological examination. OA was evaluated using the OARSI scoring system. Results: Colchicine was identified as a DMOAD candidate as it inhibited inflammatory cytokine-induced MMP13 expression in vitro, and the colchicine-administered mice with DMM presented significantly lower OARSI scores (adjusted P: 0.0242, mean difference: 1.6, 95% confidence interval (CI) of difference: 0.1651–3.035) and significantly lower synovial membrane inflammation scores (adjusted P: 0.0243, mean difference: 0.6, 95% CI of difference: 0.06158–1.138) than mice with DMM. IPA further revealed that components of the Rho signaling pathways are regulated by cytokines and colchicine. IL-1β and TNF-α activate RAC1 and SRC signals, respectively, leading to the phosphorylation of PLC-γ1 and synergistic induction of MMP13 expression. Most notably, colchicine abrogates inflammatory cytokine-induced phosphorylation of PLC-γ1, leading to the induction of MMP13 expression. Conclusions: Colchicine is a potential DMOAD candidate that inhibits MMP13 expression and consequent cartilage degradation by disrupting the SRC/RAC1-phospho-PLCγ1-Ca 2+ signaling pathway.